ULAMA PEREMPUAN DALAM DAKWAH DIGITAL: STUDI KEBANGKITAN DAN PERLAWANAN ATAS WACANA TAFSIR PATRIARKIS - Jamalul Muttaqin (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2022)
Da’wah is part of the obligation called for in the Qur'an to every ummah, not to mention women also have an important role to carry out da'wah both formally and non-formally. Women often get treatment as objects of da'wah rather than subjects of da’wah. Women even often get marginalized treatment in the context of national da'wah, because women are considered weak human beings, number two, tend to get unfair and patriarchal treatment. This phenomenon eliminates the role of women in the dynamics of the da’wah movement in Indonesia. Although slowly women began to rise from adversity and pressures. Especially the rise of Indonesian Women Ulama on social media in carrying out and delivering critical da’wah content. This research will answer these phenomenological questions. This study uses a qualitative approach. Sources of data obtained from several books, journals, articles, and other scientific works and observations in the field. This research describes three things. First, discussing the phenomenon of urban women's da'wah in the digital era. Second, revealing the religious roles of women in the public sphere. Third, describe the models of women's da'wah on social media.